Incremento del rendimiento y extracción nutrimental en jamaica mediante soluciones nutritivas - Sánchez-Prado, José Jesús; Bugarín-Montoya, Rubén; Alejo-Santiago, Gelacio; Juárez-Rosete, Cecilia Rocío; Aburto-González, Circe Aidín; Caro-Velarde, Francisco (Ecosistemas y Recursos Agropecuarios, 2019)
The concentration of the nutrient solution is an important factor that regulates the growth and development of plants in hydroponic systems. The objective of this study was to identify the best osmotic potential of the nutrient solution to increase the yield of roselle (Hibiscus sabdariffaL.) calyces and quantify the internal nutritional requirement (IR) of N, P, K, Ca and Mg. A completely randomized experimental design with four replicates was used. The treatments were the concentrations of -0.018, -0.036, -0.054, -0.072, and -0.090 MPa of Steiner’s nutrient solution in osmotic potential. The experimental unit was a pot with a plant, using red basaltic volcanic slag as substrate. Seven destructive samplings were carried out during the crop cycle. At harvest, the dry calyx production per plant was evaluated and the treatment with the highest yield was chosen to quantify the nutrient requirements of the crop. The best osmotic potential was -0.072 MPa for dry calyx production, yielding 1.98 t∙ha-1. The IR of the total biomass was 2.86, 0.50, 2.80, 1.71 and 0.54% of N, P, K, Ca and Mg, respectively, which is equivalent in kg t-1of dry calyx to: N 93.1, P 16.4, K 91, Ca 55.7, Mg 17.7. The pattern of total nutrient extraction in the aboveground biomass of the crop was in the order N > K > Ca > Mg > P. Nutrient extraction rates varied for each nutrient in the different phenological stages.